Evidence for Absolute Moral Opposition to Genetically Modified Food in the United States. (May 2016) - Scott, Sydney E.; Inbar, Yoel; Rozin, Paul
Public opposition to genetic modification (GM) technology in the food domain is widespread (Frewer et al., 2013). In a survey of U.S. residents representative of the population on gender, age, and income, 64% opposed GM, and 71% of GM opponents (45% of the entire sample) were "absolutely" opposed—that is, they agreed that GM should be prohibited no matter the risks and benefits. "Absolutist" opponents were more disgust sensitive in general and more disgusted by the consumption of genetically modified food than were non-absolutist opponents or supporters. Furthermore, disgust predicted support for legal restrictions on genetically modified foods, even after controlling for explicit risk–benefit assessments. This research suggests that many opponents are evidence insensitive and will not be influenced by arguments about risks and benefits.